2015
DOI: 10.1021/acs.nanolett.5b00490
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly into Nanoparticles Is Essential for Receptor Mediated Uptake of Therapeutic Antisense Oligonucleotides

Abstract: Antisense oligonucleotides (ASOs) have the potential to revolutionize medicine due to their ability to manipulate gene function for therapeutic purposes. ASOs are chemically modified and/or incorporated within nanoparticles to enhance their stability and cellular uptake, however, a major challenge is the poor understanding of their uptake mechanisms, which would facilitate improved ASO designs with enhanced activity and reduced toxicity. Here, we study the uptake mechanism of three therapeutically relevant ASO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 49 publications
(140 reference statements)
9
79
0
Order By: Relevance
“…Clustering or assembly of oligonucleotides often correlates with enhanced uptake and activity, across multiple size scales and likely via multiple mechanisms 48, 49. Nevertheless, in our case, despite the efficient self-assembly observed for the lipid tail conjugates, the biostable hexadecyloxypropyl conjugates showed reduced silencing efficacy in cells (Figure 5C).…”
Section: Resultsmentioning
confidence: 64%
“…Clustering or assembly of oligonucleotides often correlates with enhanced uptake and activity, across multiple size scales and likely via multiple mechanisms 48, 49. Nevertheless, in our case, despite the efficient self-assembly observed for the lipid tail conjugates, the biostable hexadecyloxypropyl conjugates showed reduced silencing efficacy in cells (Figure 5C).…”
Section: Resultsmentioning
confidence: 64%
“…However, we have recently shown that due to their amphipathic nature, PPMOs can self-assemble into micellar structures that are then taken up via receptor-mediated endocytosis [117]. Additionally, the net charge of the conjugates was dependent on the concentration.…”
Section: Uptake Pathways Of Cpp and Nucleic Acid Conjugates And Nanopmentioning
confidence: 99%
“…In gel electrophoresis experiments, the migration of the conjugates was reversed between high and low concentrations displaying a net negative charge at the low concentrations and a net positive charge at high concentrations. We speculated that this was due to the change in the balance between the ions in the medium and the charges on the conjugates enabling better shielding with counterions at lower concentrations [117]. Furthermore, self-assembly into nanoparticles was also proposed as mechanism of uptake for PNAOligo(bicycloguanidinium) conjugates [118] and the propensity to form particles was demonstrated to enhance cellular uptake even for newly developed negatively-charged ON chemistry, tcDNA [57] Different mechanisms have been proposed for CPP conjugates and nanoparticles and distinct pathways have been postulated from direct penetration to receptor-mediated endocytosis.…”
Section: Uptake Pathways Of Cpp and Nucleic Acid Conjugates And Nanopmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, our in vivo experiments, as well as other prior studies, show a mild but measurable effect of the control (Scrambled) PPMO despite a lack of in vitro activity. It is unclear whether this is related to nonspecific immune activation of the peptide itself; however, the recently reported scavenger receptor binding of PPMOs in eukaryotic cells (40) could make this a possible explanation. Recent studies by our group show that, at least in a sepsis infection model, the control PPMO acts similarly to a PBS control in terms of serum proinflammatory cytokine stimulation, and only the active PPMO significantly reduced serum proinflammatory cytokines (interleukin-6 and tumor necrosis factor alpha), presumably due to pathogen inhibition.…”
Section: Inhibition Of P Aeruginosa By Ppmosmentioning
confidence: 99%